2012
DOI: 10.1063/1.3687172
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus formation induced by dielectric barrier discharge plasma exposure in brain cancer cells

Abstract: Induction of micronucleus formation (cytogenetic damage) in brain cancer cells upon exposure of dielectric barrier discharge plasma has been investigated. We have investigated the influence of exposure and incubation times on T98G brain cancer cells by using growth kinetic, clonogenic, and micronucleus formation assay. We found that micronucleus formation rate directly depends on the plasma exposure time. It is also shown that colony formation capacity of cells has been inhibited by the treatment of plasma at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 27 publications
0
44
2
2
Order By: Relevance
“…DBD plasma had inhibitory effect on the growth of T98G cells in an exposure time-dependent manner. Plasma treatment for 30, 60, 120 and 240 s decreased the T98G cell count to 73% ( p <0.05), 66% ( p <0.05), 58% ( p <0.01), and 20% ( p <0.01), respectively, at 72 h incubation [25]. The SNU80, KB and HEK293 cells count were significantly decreased ( p <0.05) at a 240 s plasma-dose, but not after a 30 s plasma dose ( p >0.05).…”
Section: Resultsmentioning
confidence: 94%
“…DBD plasma had inhibitory effect on the growth of T98G cells in an exposure time-dependent manner. Plasma treatment for 30, 60, 120 and 240 s decreased the T98G cell count to 73% ( p <0.05), 66% ( p <0.05), 58% ( p <0.01), and 20% ( p <0.01), respectively, at 72 h incubation [25]. The SNU80, KB and HEK293 cells count were significantly decreased ( p <0.05) at a 240 s plasma-dose, but not after a 30 s plasma dose ( p >0.05).…”
Section: Resultsmentioning
confidence: 94%
“…It has been reported that the mitochondria were vulnerable to excessive H 2 O 2 insult, and this oxidative damage to the important cellular component resulted in mitochondriamediated apoptosis [33,[56][57][58][59]. In the osteoblasts treated with 1 mM H 2 O 2 for 6 h, flow cytometric analysis for JC-1 staining revealed that the mitochondrial membrane potential decreased significantly (Fig.…”
Section: Autophagy Protected Osteoblasts Against H 2 O 2 Injury Throumentioning
confidence: 92%
“…However, an innovative approach using non-thermal atmospheric pressure plasma has been developed and used in industrial applications, such as the micro-fabrication of electronic substrates789. Plasma medicine is a new field that uses non-thermal atmospheric pressure plasma for a variety of medical applications10111213141516171819, such as sterilization2021222324, wound healing2526272829, blood coagulation303132, and cancer treatment33343536373839.…”
mentioning
confidence: 99%